'Them That Runs the Country Don't Know What They're Doing': Political Dissatisfaction Amongst Members of the White Working Class. Issue 3 (August 2013) - Holmes, Mary; Manning, Nathan
There are signs that a significant number of British people do not feel that their concerns are being addressed by the mainstream parties or the political system. This paper attends to the quality of that political dissatisfaction amongst members of 'the white working classes'. There is a need to extend typical concerns about youth disengagement to adults and to consider the role that class plays. Lower participation in formal democratic processes may not mean disengagement from all forms of politics, but could have considerable consequences for who gains power and for the tone and focus of political debates and policies. Our project contributes to exploring political dissatisfaction by engaging with low wage workers in Yorkshire and the North West, where high support for the far-right BNP and low voter turnout are signs that mainstream politics and politicians are failing to impress. We asked people about their feelings in relation to mainstream politics and their concerns. These participants feel distanced from governing elites, formal political processes and old ideologies. They are searching for ways to make sense of their struggles to live a decent life, and in doing so must contend with the dominance of racist discourses.